Emptying the future: On the environmental politics of anticipation - Chris Groves (Futures, 2017)
Anticipation may be seen as structured by images and representations, an approach that has informed recent work in science and technology studies on the sociology of expectations. But anticipation, as a capacity or characteristic, is not solely manifested in the form of representations, even where such representations of the ‘not yet’ are performative in nature. It also comprises material capacities, technological, biophysical and affective in nature. The politics of anticipation is shaped by how these symbolic and material capacities, and the forms of agency they make possible, are distributed. As anticipation is an environmentally distributed capacity, it is suggested that the politics of anticipation is also an environmental politics. A conceptual framework for analysing anticipation as comprised of environmental capabilities is introduced, and fleshed out using a case study of energy infrastructure planning from the UK. Key elements of this framework include the concepts of anticipatory assemblages and future horizons or ‘styles’ of anticipation. Working through the case study as an empirical example of a conflict concerning the politics of anticipation and of ‘environments’, it is demonstrated how the relationships between styles of anticipation are materially constitutive of such conflicts.